(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
In our article, Iris Murdoch’s novel Under the Net examines the expression of human and community relationships. Murdoch shows readers how their heroes suffer, alienate, and stand out from society while offering ways to overcome these difficulties. In his novels, he makes it clear to us that it is impossible to be free without recognizing and attaining certain qualities. Murdoch wants the reader to understand that being free is very difficult and that this universal concept is related to love truth and art. Murdock’s hero seeks his freedom throughout the novel, a process very difficult and fraught with obstacles, but he manages to survive and finds his way to the sun. Murdoch sharply shows the reader that it is unthinkable to create a work of art, in this case, a novel, without finding freedom and establishing yourself in society. Murdoch learns about the bitterness and unfairness of life and wants to help his characters achieve not only physical freedom but spiritual, psychological, and emotional independence as well. This contribution aims to highlight the key element of freedom in Iris Murdoch’s first novel Under the Net and to show us once again that Murdoch stands for human freedom, freedom of thought, freedom of choice, freedom of expression, and so on, at the same time a time to recognize how difficult and difficult it is to achieve all this.